From words to action: Long-term changes in environmental literacy among EFL students - Sari Karmina; Salsabila Firda Hudaya; Lestari Setyowati; Niamika El Khoiri; Latisha Asmaak Shafie (Universitas Islam Negeri Palangka Raya, Indonesia, 2026)
While previous research has demonstrated positive short-term effects of such courses, few studies have examined changes sustained over an extended period, particularly in urban contexts facing ecological challenges. This study seeks to explore the long-term impact of integrating environmental topics into essay writing courses on EFL university students’ environmental literacy in Malang, Indonesia. Using a qualitative case study design, semi-structured interviews were conducted with ten students two years after they participated in the course. Thematic analysis revealed significant transformations across cognitive, affective, and behavioral dimensions. Students developed a deeper understanding of environmental issues, formed emotional connections to ecological concerns, and adopted sustainable practices in daily life. They also showed increased motivation to share environmental knowledge with their communities. These findings suggest that essay writing courses that incorporate environmental themes can foster meaningful, long-lasting changes in students’ attitudes and behaviors. This research contributes to the broader discourse on environmental education in EFL settings and highlights the potential of writing courses as a platform for cultivating environmental awareness and action.